TURATS DALAM PANDANGAN ZAKI NAGUIB MAHMUD (1905 - 1993) (IMPLIKASINYA PADA PEMIKIRAN KEISLAMAN DI PESANTREN SALAF INDONESIA) - Supriyanto Supriyanto (IAIN Purwokerto, 2020)
This research shows that positivistic logics in understanding turats as suggested by Zaki has an implication on the development of thinking among pesantrens. His positivistic ideas are used by pesantren scholars. The concept of modernization in education supported by abroad graduates, especially Europe, and developed curriculum responding to modern need are the portraits that salaf pesantren are dynamic in relation to the concept of Akhdzu bi al-Jadid al-Ashlah. Logical contribution of science has been accepted in the logical thinking of salaf pesantens. One of them is that there has been a law of using certain medicine to put off menstruation stating that it is not prohibited, although such a law has not been discussed in classical books. However, old traditions like respecting teachers (ta'dzim), studying classical books using classical and personal system (sorogan and bandungan), and asking blessing from kiai are still practiced. This is the real implementation of the concept of al-Muhafadzah ‘ala al-Qadim ash-Shalih.